A study on the traditional culture of the Korean ethnic group in Yanji, China - Hassan, Aminuddin; Ghazali, Siti Sabihah; Chen, Zhuo (Human Resource Management Academic Research Society, 2024)
The Korean ethnic group in China boasts a rich and vibrant traditional national culture with a long history. However, the rapid economic development has led to significant sinicization and severe damage to their national culture. The influx of transnational labor families has resulted in an intergenerational rupture in the transmission of this cultural heritage. Persistent conflicts and population movements have contributed to the erosion of national characteristics. Hence, the preservation and safeguarding of Korean traditional culture becomes imperative. This study primarily employed the questionnaire method, interview method, and ethnographic research to collect firsthand data. Through a comparative analysis of survey data from various perspectives and levels.This study focuses on etiquette culture, clothing culture, food culture, residential culture, and folk culture.It aims to explore the current state of traditional culture among ethnic minorities in Korean-inhabited areas. The findings of this research hold theoretical significance, providing valuable references for interdisciplinary studies in education, sociology, ethnology, and other related disciplines.